IMPLEMENTATION OF DIGITAL MARKETING AS A STRATEGY TO INCREASE MR BUTIK STORE SALES - Muhammad Ramdhan; Rahayu, Suharni (BAIK Publishers, 2025)
This study aims to analyze the implementation of digital marketing in an effort to increase sales in a store. The type of research used is qualitative research with a case study approach. The main informants in this study were the store owner and employees, while the supporting informant was a customer. Data collection was carried out through three techniques, namely interviews, observations, and literature studies. This research was conducted at MR Butik Store. The results of the study indicate that the MR Butik Store has consistently implemented a digital marketing strategy. This allows for increased interactivity, better information provision, service personalization, and inclusion of market trends. The implementation of digital marketing contributes to increased accuracy in determining selling prices, cost efficiency, and increased demand and sales volume.